2018
DOI: 10.1039/c7sc03018e
|View full text |Cite
|
Sign up to set email alerts
|

Doping palladium with tellurium for the highly selective electrocatalytic reduction of aqueous CO2 to CO

Abstract: The doping of Pd with a small amount of Te can selectively convert CO2 to CO with a low overpotential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(57 citation statements)
references
References 31 publications
(23 reference statements)
4
51
0
Order By: Relevance
“…However, as the binding energies of Al 2p and Pt 4f overlap, the high amount of Al precludes any clear quantification of Pt species. For the Pd/CeAl catalyst (Figure 5b), the two peaks observed can be attributed to Pd 3d 5/2 (at 334.9 eV) and Pd 3d 3/2 (at 340.4 eV), which correspond to Pd 0 [90]. The binding energy of Pd 3d 5/2 was at 334.9 eV, indicating the presence of Pd in metallic state, and with an atomic surface concentration equal to 0.11%.…”
Section: Characterizations Resultsmentioning
confidence: 94%
“…However, as the binding energies of Al 2p and Pt 4f overlap, the high amount of Al precludes any clear quantification of Pt species. For the Pd/CeAl catalyst (Figure 5b), the two peaks observed can be attributed to Pd 3d 5/2 (at 334.9 eV) and Pd 3d 3/2 (at 340.4 eV), which correspond to Pd 0 [90]. The binding energy of Pd 3d 5/2 was at 334.9 eV, indicating the presence of Pd in metallic state, and with an atomic surface concentration equal to 0.11%.…”
Section: Characterizations Resultsmentioning
confidence: 94%
“…Tailoring the surface tensile strain to alter the electronic structures can optimize the performance of Pd electrocatalysts . Doping Pd with Tellurium (Te) can stabilize the CO 2 .− intermediate to favor the desired carbon dioxide reduction reaction (CO 2 RR) and destabilize the adsorption of H to suppress unwanted H 2 evolution . Varying the particle size to change the ratio of the corner, edge, as well as terrace sites and alloying with a second metal to adjust the atomic arrangement can modulate the adsorption of CO 2 .− intermediate to accelerate the CO 2 RR so as to regulate the catalytic activity.…”
Section: Figurementioning
confidence: 99%
“…Previous studies have reported that the first electron transfer step of *CO 2 +e − →*CO 2 .− is generally regarded as the rate‐determining step (RDS) and results in a theoretical Tafel slope of 118 mV dec −1 (Scheme S1) . To obtain insights into the mechanism of CO formation on these electrodes, Tafel plots, an indication of kinetics for CO formation, were tested (Figure a).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations